SMES' VIEW ON PARTICIPATION BANKS: A RESEARCH IN ISPARTA (Third Sector Social Economic Review, 2019)
The aim of this research is to reveal the SMEs' view of participation banks. The research was carried out in Isparta between March and May 2019, with 315 enterprises under 250 employees. According to the results, the highest scoring evaluation; SMEs have stated that they can work with participation banks if they offer low interest loans. According to the second answer, SMEs stated that they can work with participation banks if they have attractive dividend rates and payment opportunities. According to the third highest answer, SMEs stated that they can work with participation banks when they think they are commercially profitable. The belief that participation banks carry out interest-free transactions as claimed is the lowest score with 2.76 / 5 points. Businesses do not pay much attention to the separation of participation bank or traditional bank when it comes to business interests. Choices based on religious phenomena are not seen as the main determinant of whether or not to work with participation banks. At the other stage of the analysis, it was examined whether there is a statistically significant difference in the opinions of SMEs about participation banking according to demographic factors.
Keywords: SME’s View on Participation Banks; Participation Banking; Kruskal-Wallis